Social Media: Opportunity or threat to public health in context of Nepal - Thakur, Dip Narayan (Health Prospect, 2017)
Social media, one of the greatest tools for sharing information, are used for various purposes in health like educational and promotional activities, communication - of research findings and during crisis readiness. In addition, online conference and webinar for health purpose, e-procurement of health commodities and telemedicine are some domains where we use social media. In contrast to these, it brings out various ill impacts on health directly or indirectly, such as cyberbullying, depression, anxiety, sleep disorders, physical inactivity- a boost factor for non-communicable diseases and internet addiction. As this field is new in health and being used innovatively, issues of their effectiveness, privacy and confidentiality begin to rise. Moreover, authenticity of the health information available on social media is another issue, all of which need guidance by evidence based acts and regulations. Else, it may harm the belief of users on the platform, which is the future for health information sharing. With very few researches done regarding the use of internet and social media, and increasing addiction towards them possesses an extra threat to health in Nepal. Hence, research regarding possible hazards of social media use and relative effectiveness of social media over other communication channel is needed, to develop necessary strategies to overcome possible threats to health and utilize social media for health to its optimum potential.